Libraries : global reach, local touch / edited by Kathleen de la Peña McCook, Barbara J. Ford and Kate Lippincott. Chicago, London : American Library Association, 1998. v, 256 p. ISBN 0-8389-0738-5 (Información, cultura y sociedad, 2014)
Reseña.